Navigation for a mobile robot to inspect aircraft - Mansakul, Thanavin; Fan, Ip-Shing; Tang, Gilbert (Institute of Electrical and Electronics Engineers (IEEE), 2023)
Preflight inspection is an important part of aircraft maintenance, as it does not affect only safety but also expenditure. In order to reduce the risks from human errors and the cost of operation, a mobile robot is introduced as an effective solution. This research examines navigation for aircraft inspection using a mobile robot. The two path planning methods, Dijkstra with DWA and A* with TEB, are compared by navigation performance in the simulation and three environments which are office, atrium, and hangar, to ensure that the robot is able to handle a variety of situations. In addition, an ultrasonic sensor was installed to perform obstacle avoidance and support LIDAR when it failed. The result is that both algorithms have their advantages depending on the purpose; if an accurate position is required, A* with TEB should be selected, while Dijkstra with DWA offers a smooth path and less time spent in small and complex environments. The notable parameters in navigation for the mobile robot, TurtleBot3, are presented, and limitations are detailed. The use of the autonomous mobile robot could support the operation with high precision and repeatability.
Keywords: Autonomous mobile robot; TurtleBot3; aircraft inspection; navigation; path planning; A*; Dijkstra; Dynamic-Window Approach (DWA); Timed Elastic Band (TEB)